2009
DOI: 10.1681/asn.2008020238
|View full text |Cite
|
Sign up to set email alerts
|

HNF-1β Regulates Transcription of the PKD Modifier Gene Kif12

Abstract: Hepatocyte nuclear factor-1␤ (HNF-1␤) is a transcription factor that regulates gene expression in the kidney, liver, pancreas, and other epithelial organs. Mutations of HNF-1␤ lead to a syndrome of inherited renal cysts and diabetes and are also a common cause of sporadic renal dysplasia. The full complement of target genes responsible for the functions of HNF-1␤, however, is incompletely defined. Using a functional genomics approach involving chromatin immunoprecipitation and promoter arrays, combined with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 22 publications
2
45
0
1
Order By: Relevance
“…33 Recently, chromatin immunoprecipitation array experiments were used to seek gene targets for Hnf1b in mouse kidneys. 34 Consistent with our observation of HNF1-binding sites in human FXYD2, the mouse im- Three different splice variants are recognized for human FXYD2 (Figure 3A), the main ones being variants a and b. 35 An immunohistochemical study of rat kidneys reported that TALs in the inner medullary stripe expressed both Fxyd2a and b isoforms, whereas Fxyd2a was predominant in proximal tubules and Fxyd2b in DCTs, connecting tubules, and other TAL.…”
Section: Discussionsupporting
confidence: 86%
“…33 Recently, chromatin immunoprecipitation array experiments were used to seek gene targets for Hnf1b in mouse kidneys. 34 Consistent with our observation of HNF1-binding sites in human FXYD2, the mouse im- Three different splice variants are recognized for human FXYD2 (Figure 3A), the main ones being variants a and b. 35 An immunohistochemical study of rat kidneys reported that TALs in the inner medullary stripe expressed both Fxyd2a and b isoforms, whereas Fxyd2a was predominant in proximal tubules and Fxyd2b in DCTs, connecting tubules, and other TAL.…”
Section: Discussionsupporting
confidence: 86%
“…Cys1 is responsible for congenital polycystic kidney (CPK) disease (Tao et al, 2009) and is involved in ciliogenesis and polarization of cholangiocytes (Raynaud et al, 2011), whereas Glis3 is implicated in polycystic disease in both kidney (Kang et al, 2009a) and pancreas (Kang et al, 2009b). Among these genes, Kif12, Pkhd1, Pkd2 and Bicc1 were identified as direct Hnf1b targets in the kidney (Gong et al, 2009;Gresh et al, 2004;Verdeguer et al, 2010). Thus, we analyzed whether Hnf1b could be a major regulator of these genes in the pancreas by ChIP experiments on E12.5 pancreata (Fig.…”
Section: Hnf1b Controls Duct Morphogenesis By Regulating Cystic Diseamentioning
confidence: 99%
“…During kidney development, the gene is expressed in the ureteric bud, in the comma-and S-shaped bodies, and then in the proximal and distal tubules but not in the glomerulus (9). Kidney-specific inactivation of Hnf1B in the mouse leads to cystic disease, and HNF1␤ was shown to bind directly DNA elements that regulate the expression of genes whose mutations are responsible for cystic kidney diseases (Nphp1, polaris, Umod, Pkhd1, and Pkd2) (10) or of a gene identified as a candidate modifier in a mouse model of cystic kidney disease (Kif12) (11). Here we report on HNF1B mutation screening in a series of 377 unrelated patients who presented with various kidney phenotypes, giving special attention to the prenatal renal phenotypes.…”
mentioning
confidence: 99%